Sodium ion battery electrolyte additive, electrolyte and sodium ion battery
By using electrolyte additives with specific structures in sodium ion batteries, a stable interface mask is formed, which solves the problems of low first charge and discharge efficiency and poor circulation performance of sodium ion batteries, achieving higher charge and discharge efficiency and capacity retention rate, reducing impedance growth and gas production.
Patent Information
- Application Number
- CN202310042506.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-28
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-01-28
AI Technical Summary
The current sodium ion batteries have low first charge and discharge efficiency and first discharge capacity and poor circulation performance, resulting in rapid capacity decay and increased impedance during use.
A sodium ion battery electrolyte additive is used, and the structural formula of the additive is R1-N-C=O-SO2-R2, where R1 and R2 are substituted or unsubstituted alkyl or unsaturated hydrocarbon groups. The additive forms a stable interface film at the electrode/electrolyte interface to reduce the consumption of active sodium and improve the first charging efficiency and capacity of the battery.
The first charge and discharge efficiency and first discharge capacity of sodium ion batteries are improved, the battery cycle capacity attenuation is suppressed, the cycle gas production and impedance growth is reduced, and the stable performance of the battery is ensured at high temperatures.
Smart Images

Figure CN117096435B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery electrolyte additive, an electrolyte and a sodium ion battery. Background Art
[0002] Due to the limited global reserves of lithium resources, the cost of lithium-ion batteries has increased significantly. However, sodium resources are more abundant, their material costs are lower, and they can technically achieve similar functions as lithium-ion batteries. Therefore, the development of high-performance sodium-ion batteries will help alleviate the resource problems of the new energy industry.
[0003] Like lithium-ion batteries, sodium-ion batteries are also composed of positive electrodes, negative electrodes, electrolytes and diaphragms. Among them, the electrolyte, as a carrier for the transmission of sodium ions between the positive and negative electrodes, needs to be insulated from the electrons between the positive and negative electrodes to prevent the electrolyte from continuously undergoing redox decomposition reactions. However, unlike the graphite negative electrode of lithium-ion batteries, the negative electrode of sodium-ion batteries usually uses amorphous carbon materials with a large specific surface area, such as hard carbon, as the negative electrode. The electrolyte consumes a lot of electrolyte film formation on the hard carbon surface, and the passivation film is thick and not dense enough, resulting in a low initial charge and discharge efficiency of the battery. During the cycle, more interfacial side reactions will occur, resulting in a rapid decay of the cycle capacity accompanied by gas production and impedance growth, and satisfactory electrochemical performance cannot be obtained. Summary of the invention
[0004] In view of the above analysis, the embodiments of the present invention aim to provide a sodium ion battery electrolyte additive, an electrolyte and a sodium ion battery, so as to solve at least one of the problems of the existing sodium ion battery, such as low first charge and discharge efficiency and first discharge capacity, and poor cycle performance.
[0005] In one aspect, the present invention provides a sodium ion battery electrolyte additive, wherein the additive has a structural formula as shown in formula (I):
[0006]
[0007] Wherein, R1 is selected from a substituted or unsubstituted C1-C5 alkyl group, a substituted or unsubstituted C2-C5 unsaturated hydrocarbon group.
[0008] Furthermore, the R1 is selected from a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C2-C3 unsaturated hydrocarbon group.
[0009] Furthermore, the additive is selected from one or more of compounds 1 to 8, and the structural formulas of compounds 1 to 8 are as follows:
[0010]
[0011] In a second aspect, the present invention provides a sodium ion battery electrolyte, wherein the electrolyte comprises the additive, a sodium salt and an organic solvent.
[0012] Furthermore, the mass of the additive accounts for 0.01-5% of the total mass of the electrolyte.
[0013] Furthermore, the concentration of the sodium salt in the electrolyte is 0.2-2 mol / L.
[0014] Furthermore, the sodium salt is selected from one or more of sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, sodium methanesulfonate, sodium trifluoromethanesulfonate, sodium bisoxalatoborate, sodium difluorooxalatoborate, sodium difluorophosphate, sodium difluorobisoxalatophosphate, sodium bis(fluorosulfonyl)imide and sodium bis(trifluoromethylsulfonyl)imide.
[0015] Furthermore, the organic solvent is selected from one or more of carboxylates, ethers, cyclic carbonates, chain carbonates and heterocyclic compounds.
[0016] In a third aspect, the present invention provides a sodium ion battery comprising the electrolyte, a positive electrode, a negative electrode and a separator.
[0017] Furthermore, the charging voltage of the sodium ion battery is ≤4.5V.
[0018] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0019] (1) The additive of the present invention can improve the initial charge and discharge efficiency and initial discharge capacity of the sodium ion battery, and also has good cycle performance, which is specifically manifested in inhibiting the battery cycle capacity decay, reducing cycle gas generation and impedance growth;
[0020] (2) The additives described in the present invention can form a stable interface film (SEI) at the electrode / electrolyte interface. The interface film is a composite structure of organic and inorganic substances. The side close to the electrolyte is a loose and porous part dominated by organic substances, which is conducive to the infiltration of the electrolyte and the transmission of sodium ions. The side close to the electrode material is a dense part dominated by inorganic substances, which is conducive to inhibiting the occurrence of side reactions of the electrolyte. The additives can reduce the consumption of active sodium during the negative electrode film formation process, thereby facilitating the improvement of the first charge efficiency and the first capacity. The NC=O structure in formula (I) is thermally stable. The structure of the present invention is good, and the introduction of sulfur, nitrogen and oxygen elements enriches the electrode / electrolyte interface film components, further improving the chemical stability and thermal stability of the interface film, thereby facilitating the inhibition of impedance growth during the sodium ion battery cycle. At the same time, NC=O is not easy to produce gas at high temperatures, which is beneficial to improving the cycle gas production of the sodium ion battery. In addition, the sulfonimide structure on the side chain of formula (I) can improve the structural toughness and stability of the SEI film, inhibit the interface film "rupture-repair" side reaction caused by the volume change of the material during the cycle, and is beneficial to inhibiting the loss of active sodium during the cycle of the sodium ion battery.
[0021] (3) The additive of the present invention is applied to sodium ion batteries, and the sodium ion batteries have good initial charge and discharge efficiency and initial discharge capacity at high voltage, and also have good cycle performance, which is specifically manifested in inhibiting battery cycle capacity attenuation, reducing cycle gas production and impedance growth;
[0022] (4) The mass of the additive described in the present invention accounts for 0.01-5% of the total mass of the electrolyte. This is because when the content of the additive is less than 0.01%, the film formation of the compound of formula (I) is poor, and the protection of the electrode electrolyte interface is relatively weak, thereby inhibiting the nitrogen-containing heterocyclic group from improving the film formation efficiency and cycle performance; when the content of the additive exceeds 5%, the film formation of the compound of formula (I) becomes thicker, which will inhibit the sulfonamide group from improving the toughness and stability of the SEI film structure, resulting in the intensification of the "rupture-repair" side reaction of the interface film caused by the change in material volume during the cycle, resulting in increased impedance and gas generation;
[0023] (5) The sodium ion battery of the present invention has an initial charge and discharge efficiency of ≥83.3%, an initial capacity of ≥1454.6 mAh, a capacity retention rate of ≥85.8% after 500 cycles, an internal resistance growth rate of ≤22.4%, and a gas expansion rate of 5.8-24.5%.
[0024] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be achieved and obtained through the contents particularly pointed out in the description. DETAILED DESCRIPTION
[0025] A specific embodiment of the present invention discloses a sodium ion battery electrolyte additive, wherein the additive has a structural formula as shown in formula (I):
[0026]
[0027] Wherein, R1 is selected from a substituted or unsubstituted C1-C5 alkyl group, a substituted or unsubstituted C2-C5 unsaturated hydrocarbon group.
[0028] The additive of the present invention can form a stable interface film (SEI) at the electrode / electrolyte interface. The interface film is a composite structure of organic and inorganic substances. The side close to the electrolyte is a loose porous part dominated by organic substances, which is conducive to the infiltration of the electrolyte and the transmission of sodium ions. The side close to the electrode material is a dense part dominated by inorganic substances, which is conducive to inhibiting the occurrence of side reactions of the electrolyte. The additive can reduce the consumption of active sodium during the negative electrode film formation process, thereby facilitating the improvement of the first charge efficiency and the first capacity. The thermal stability of the NC=O structure in formula (I) is The invention discloses a novel nanostructured carbon nanotube with a good structure and good thermal conductivity. The introduction of sulfur, nitrogen and oxygen elements enriches the electrode / electrolyte interface film components, further improves the chemical stability and thermal stability of the interface film, thereby helping to inhibit the impedance growth during the sodium ion battery cycle. At the same time, NC=O is not easy to produce gas at high temperatures, which is beneficial to improving the cycle gas production of the sodium ion battery. In addition, the sulfonimide structure on the side chain of formula (I) can improve the structural toughness and stability of the SEI film, inhibit the interface film "rupture-repair" side reaction caused by the volume change of the material during the cycle, and help to inhibit the loss of active sodium during the cycle of the sodium ion battery.
[0029] Specifically, the R1 is selected from a substituted or unsubstituted C1-C3 alkyl group and a substituted or unsubstituted C2-C3 unsaturated hydrocarbon group.
[0030] Specifically, the additive is selected from one or more of compounds 1 to 8, and the structural formulas of compounds 1 to 8 are as follows:
[0031]
[0032] Another embodiment of the present invention provides a sodium ion battery electrolyte, wherein the electrolyte comprises the additive, a sodium salt and an organic solvent.
[0033] Specifically, the mass of the additive accounts for 0.01-5% of the total mass of the electrolyte.
[0034] Exemplarily, the mass of the additive accounts for 0.01%, 0.05%, 0.10%, 0.15%, 0.20%, 0.25%, 0.30%, 0.35%, 0.40%, 0.45%, 0.50%, 0.55%, 0.60%, 0.65%, 0.70%, 0.75%, 0.80%, 0.85%, 0.90%, 0.95%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0% of the total mass of the electrolyte.
[0035] It should be noted that the inventors found in the experimental process that although the compound shown in formula (I) can improve the initial charge and discharge efficiency and cycle performance of the sodium ion battery at high voltage and reduce the cycle gas production, when the mass of the electrolyte additive accounts for more than 5% or less than 0.01% of the total mass of the electrolyte, the high and low temperature performance of the sodium ion battery at high voltage cannot reach the best. After a large number of experimental analyses, the inventors found that when the content of the compound of formula (I) is too low or too high, it is not conducive to improving the performance of the battery, especially when the content of the compound of formula (I) is too high, the cycle performance of the battery will be significantly reduced. Comprehensive analysis shows that the mass of the additive of the present invention is selected to account for 0.01-5% of the total mass of the electrolyte, which can further improve the initial charge and discharge efficiency and cycle performance of the sodium ion battery and inhibit the battery cycle gas production.
[0036] Specifically, the concentration of the sodium salt in the electrolyte is 0.2-2 mol / L.
[0037] Exemplarily, the concentration of the sodium salt in the organic solvent is 0.2 mol / L, 0.4 mol / L, 0.6 mol / L, 0.8 mol / L, 1.0 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L, or 2.0 mol / L.
[0038] It should be noted that the concentration of sodium salt in the electrolyte in the present invention is 0.2-2 mol / L. If the concentration is too low, the conductivity is too low, the battery impedance is too large, and it is not conducive to ion transmission. If the concentration is too high, the viscosity is too high, and it is not easy to wet the electrode, so the battery cannot be charged and discharged or sodium precipitation occurs.
[0039] Specifically, the sodium salt is selected from one or more of sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium tetrafluoroborate (NaBF4), sodium methanesulfonate (NaCH3SO3), sodium trifluoromethylsulfonate (NaCF3SO3), sodium bis(oxalatoborate) (NaC4BO8), sodium difluorooxalatoborate (NaC2BF2O4), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFBP), sodium bis(fluorosulfonyl)imide (NaFSI) and sodium bis(trifluoromethylsulfonyl)imide (NaTFSI).
[0040] Specifically, the organic solvent is selected from one or more of carboxylates, ethers, cyclic carbonates, chain carbonates and heterocyclic compounds.
[0041] Specifically, the electrolyte also includes other raw materials, and the other raw materials are selected from at least one of vinylene carbonate (VC), vinylene carbonate (VEC), fluoroethylene carbonate (FEC), vinyl sulfite (ES), 1,3-propane sultone (PS), 1,3-propylene sultone (PST), 1,4-butane sultone (BS) and diethylene sulfate (DTD), 4-methylethylene sulfate, and propylene sulfate (PCS).
[0042] It should be noted that the electrolyte described in the present invention is applied to sodium ion batteries, and the sodium ion batteries have good initial charge and discharge efficiency and initial discharge capacity under high voltage, and also have good cycle performance, which is specifically manifested in inhibiting battery cycle capacity attenuation, reducing cycle gas production and impedance growth.
[0043] Another embodiment of the present invention discloses a sodium ion battery, comprising the above-mentioned electrolyte, a positive electrode, a negative electrode and a separator.
[0044] It should be noted that the positive electrode, negative electrode and separator in the present invention are all made of materials from the prior art, and the present invention does not impose any special limitation thereto.
[0045] Exemplarily, the positive electrode material is made of sodium copper iron manganese oxide, and its chemical formula is: Na x Cu y Fe z Mn a M bO2, wherein M is an element for doping and replacing the transition metal position, specifically one or more of Li, Ni, Mg, Zn, Co, Al, Zr, and Ti; x, y, z, a, and b are the molar percentages of the corresponding elements, respectively, wherein 0.6<x<1.2, 0<y<0.5, 0<z≤0.5, 0<a≤0.8, 0≤b≤0.5; y+z+a+b=1, and each element in the chemical formula satisfies charge balance; preferably, x=1, y=z=a=1 / 3, and b=0, and the negative electrode is a hard carbon negative electrode material.
[0046] For example, the positive electrode active material may be at least one of layered oxides, polyanions, and Prussian blue / white materials. The negative electrode active material may be at least one of carbon-based materials, titanium-based materials, alloy materials, and organic compounds.
[0047] It should be noted that the sodium ion battery described in the present invention has good initial charge and discharge efficiency and initial discharge capacity under a high voltage system, and also has good cycle performance, which is specifically manifested in inhibiting battery cycle capacity attenuation, reducing cycle gas production and impedance growth.
[0048] Example 1
[0049] Compound 1 of the present embodiment was prepared by the following method: 81.5 g (0.5 mol) of acesulfame was added to a 500 mL reaction bottle, 200 mL of deionized water was added, 27.56 g (0.26 mol) of sodium carbonate was added in batches, and the reaction was stirred until the system was not acidic. The mixture was dried under reduced pressure to obtain a white solid, 200 mL of dimethyl carbonate was added, stirred to fully dissolve, and filtered to obtain a clear solution after standing, and dried under reduced pressure to obtain a white solid, and the mixture was recrystallized from a dimethyl carbonate / toluene mixed solvent, filtered, and dried under reduced pressure to obtain a white solid product, which was Compound 1.
[0050] Example 2
[0051] Compounds 2 to 4 of this example were prepared by the following method:
[0052] 100 g of compound 1 prepared in Example 1 was placed in a reaction chamber, fluorine gas and nitrogen gas were mixed in a ratio of 1:4, and then introduced into the reaction chamber through a fluorine / nitrogen metering device at a flow rate of 500 L / h. The frequency of the infrared generator was adjusted to 5×10 13Hz, control the reaction temperature to 80°C, and the pressure to 0.6MPa for fluorination reaction. After 20 hours, the reaction is completed, the product is released, and the incompletely reacted tail gas enters the tail gas treatment device for treatment. The mixed product is dissolved in 100ml of 5% hydrochloric acid solution, and the components are separated by "cooling-crystallization-filtration". Solid substances are precipitated at -5 to -10°C, -20 to -22°C, and -26 to -28°C, respectively. After nuclear magnetic resonance analysis, the three temperatures are identified to correspond to compound 4, compound 2, and compound 3, respectively. The obtained compounds are vacuum dried at 60°C to obtain 15.2g of compound 2, 18.1g of compound 3, and 16.7g of compound 4, respectively.
[0053] Example 3
[0054] The compound 5 of this example was prepared by the following method: 20 g of the compound 1 prepared in Example 1 was placed in a reaction chamber, hydrogen and nitrogen were mixed in a ratio of 1:4, and then introduced into the reaction chamber through a hydrogen / nitrogen metering device at a flow rate of 200 L / h, and the frequency of the infrared generator was adjusted to 3×10 13 Hz, the reaction temperature was controlled to be 100°C and the pressure was controlled to be 0.5MPa for hydrogenation reaction. After the reaction was completed in 10 hours, the product was released, and the incompletely reacted tail gas entered the tail gas treatment device for treatment. The solid substance was compound 5.
[0055] Example 4
[0056] Compounds 6 to 8 of this example were prepared by the following method: only the reactant compound 1 was replaced with compound 2, compound 3 or compound 4, and the rest was the same as in Example 3, to obtain compound 6, compound 7 or compound 8, respectively.
[0057] Example 5 Preparation of electrolyte
[0058] Propylene carbonate (PC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of PC:DEC:EMC=1:1:1 to obtain a solvent, and then sodium hexafluorophosphate (NaPF6) is added, the concentration of sodium hexafluorophosphate (NaPF6) is 1 mol / L, and then compound 1 accounting for 1% of the total mass of the electrolyte is added to obtain an electrolyte.
[0059] Examples 6 and 7
[0060] In Examples 6 and 7, only the addition amount of compound 1 was changed, and the rest was the same as in Example 5. The electrolyte was prepared, and the composition of each raw material was shown in Table 1.
[0061] Embodiments 8 to 17
[0062] The preparation of the electrolytes of Examples 8 to 17 is specifically described in Example 11, and the composition of each raw material is shown in Table 1.
[0063] Table 1
[0064] Group Other raw materials additive Mass content of additives Example 5 - Compound 1 1% Example 6 - Compound 1 0.01% Example 7 - Compound 1 5% Example 8 2% FEC Compound 1 1% Example 9 2% FEC Compound 2 1% Example 10 2% FEC Compound 3 1% Embodiment 11 2% FEC Compound 4 1% Example 12 2% FEC Compound 5 1% Example 13 2% FEC Compound 6 1% Embodiment 14 2% FEC Compound 7 1% Embodiment 15 2% FEC Compound 8 1% Example 16 2% FEC Compound 1 0.01% Embodiment 17 2% FEC Compound 1 5% Comparative Example 1 - - - Comparative Example 2 2% FEC - - Comparative Example 3 2% FEC Compound 1 0.001% Comparative Example 4 2% FEC Compound 1 6% Comparative Example 5 - Compound 1 0.001% Comparative Example 6 - Compound 1 6%
[0065] Comparative Examples 1 to 6
[0066] The preparation methods of the electrolytes in Comparative Examples 1 to 6 are the same as those in Example 5, with the differences shown in Table 1.
[0067] Preparation of sodium ion batteries
[0068] The electrolytes prepared in Examples 5-17 and Comparative Examples 1-6 were made into sodium ion batteries, and the specific preparation method was as follows:
[0069] (1) The copper-iron-manganese-sodium ternary material NaCu 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, conductive agent SuperP, adhesive PVDF and carbon nanotubes (CNT) were mixed evenly in a mass ratio of 97.5:1.5:1.5:0.5 to form a sodium ion battery positive electrode slurry with a certain viscosity, which was coated on the aluminum foil for current collector. The coating amount was 32 mg / cm 2 , dried at 85°C and then cold pressed; then trimmed, cut into pieces, and slit, and then dried at 85°C for 4 hours under vacuum conditions, and the tabs were welded to produce a positive electrode sheet for a sodium ion battery that meets the requirements;
[0070] (2) Hard carbon, conductive agent SuperP, thickener CMC, and adhesive SBR (styrene-butadiene rubber latex) were mixed in a mass ratio of 95:1.4:1.4:2.2 to make a slurry, mixed evenly, and coated on both sides of the copper foil with the mixed slurry and dried at 85°C. The coating amount was 18 mg / cm 2 ; Trimming, cutting, and slitting are performed, and after slitting, the negative electrode sheet of the sodium ion battery that meets the requirements is made by drying at 110°C for 4 hours under vacuum conditions, and welding the tabs;
[0071] (3) The positive electrode sheet, negative electrode sheet and separator prepared above were laminated to form a sodium ion battery with a thickness of 6 mm, a width of 60 mm and a length of 66 mm. The battery was vacuum baked at 85°C for 24 hours, and the electrolytes prepared in Examples 5-17 and Comparative Examples 1-6 were injected respectively. After standing for 24 hours, the battery was charged to 2.5 V with a constant current of 0.1 C (150 mA), and charged to 4.2 V with a constant current and constant voltage of 0.3 C (450 mA) until the current dropped to 0.05 C (75 mA). The sum of the two-step charging capacity was the initial charging capacity C0. The battery was then discharged to 2.0 V with 0.2 C (300 mA). The discharged capacity was the initial discharge capacity C1. Finally, the battery was charged to 3.5 V with 0.2 C (300 mA) to complete the preparation of the sodium ion battery.
[0072] The sodium ion batteries made of the electrolytes of Examples 5-17 and Comparative Examples 1-6 were subjected to battery performance cycle tests. The test results are shown in Table 2, wherein the first charge and discharge efficiency = first discharge capacity C1 / first charge capacity C0*100%.
[0073] The battery performance cycle test conditions are as follows:
[0074] The prepared sodium ion battery was placed in a 45°C constant temperature box and subjected to a 1C constant current constant voltage charge / 1C constant current discharge cycle test in the 2-4.2V voltage range. The constant current constant voltage charge cutoff current was 0.05C, and each step of charging and discharging was left alone for 2 minutes. The discharge capacity, impedance and volume of the battery before cycling, and the discharge capacity, impedance and volume after 500 cycles were recorded.
[0075] The capacity retention rate, impedance growth rate and gas expansion rate of high temperature cycle are calculated as follows:
[0076] Capacity retention rate = discharge capacity after cycle / discharge capacity before cycle × 100%;
[0077] Impedance growth rate = (impedance after cycle - impedance before cycle) / impedance before cycle × 100%;
[0078] Swelling ratio = (battery volume of battery after cycle - initial battery volume) / initial battery volume x 100%.
[0079] Table 2
[0080]
[0081] From the results in Table 2, it can be seen that the various properties of the sodium ion batteries prepared in Examples 5-17 are better than those in Comparative Examples 1-6, which indicates that the compound represented by formula (I) of the present invention can form a stable interface film (SEI) at the electrode / electrolyte interface. The interface film is a composite structure of organic and inorganic substances. The side close to the electrolyte is a loose porous part dominated by organic substances, which is beneficial to the infiltration of the electrolyte and the transmission of sodium ions. The side close to the electrode material is a dense part dominated by inorganic substances, which is beneficial to inhibiting the occurrence of side reactions of the electrolyte. The additive can reduce the consumption of active sodium during the negative electrode film formation process, thereby facilitating the initial charging efficiency. and the improvement of the first capacity, the NC=O structure in formula (I) has good thermal stability, and the introduction of sulfur, nitrogen and oxygen elements enriches the electrode / electrolyte interface film components, further improving the chemical stability and thermal stability of the interface film, which is beneficial to inhibiting the impedance growth during the cycle of the sodium ion battery. At the same time, NC=O is not easy to produce gas at high temperatures, which is beneficial to improving the cyclic gas production of the sodium ion battery. In addition, the sulfonimide structure on the side chain of formula (I) can improve the structural toughness and stability of the SEI film, inhibit the "rupture-repair" side reaction of the interface film caused by the volume change of the material during the cycle, and is beneficial to inhibiting the loss of active sodium during the cycle of the sodium ion battery.
[0082] Comparing Examples 5 to 7 with Comparative Examples 1, 5 and 6, it can be found that when the additive content is less than 0.01%, the first charge and discharge efficiency, the first discharge capacity and the cycle performance of the sodium ion battery cannot reach the optimal state. This is because when the additive content is less than 0.01%, the film formation of the compound of formula (I) is poor, and the protection of the electrode electrolyte interface is relatively weak, thereby inhibiting the nitrogen-containing heterocyclic group from improving the film formation efficiency and cycle performance; when the additive content exceeds 5%, the film formation of the compound of formula (I) becomes thicker, which will inhibit the sulfonamide group from improving the toughness and stability of the SEI film structure, resulting in the intensification of the "rupture-repair" side reaction of the interface film caused by the change in material volume during the cycle, thereby increasing the impedance and generating gas. Based on the above analysis, the mass of the additive in the present invention accounts for 0.01 to 5% of the total mass of the electrolyte.
[0083] By comparing Example 8, Examples 16 to 17 with Comparative Examples 2 to 4, the above conclusion can also be obtained.
[0084] Comparing Examples 8 to 15 with Comparative Example 2, the sodium ion batteries containing the additive of the present invention have significantly increased first charge and discharge efficiency and first discharge capacity, and significantly improved cycle performance, indicating that the additive of the present invention improves the film formation quality.
[0085] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A sodium ion battery, characterized in that: Including electrolyte, positive electrode, negative electrode and separator; The electrolyte comprises an additive, a sodium salt and an organic solvent, wherein the concentration of the sodium salt in the electrolyte is 0.2 to 2 mol / L; the additive is selected from one or more of compounds 2 to 7, and the structural formula is shown below: The mass of the additive accounts for 0.01-0.40% of the total mass of the electrolyte; The sodium ion battery has good initial charge and discharge efficiency and initial discharge capacity under high pressure, and also has good cycle performance. The initial charge and discharge efficiency of the sodium ion battery is ≥83.3%, the initial capacity is ≥1454.6 mAh, and after 500 cycles, the capacity retention rate is ≥85.8%, the internal resistance growth rate is ≤22.4%, and the inflation rate is 5.8-24.5%; The sodium salt is selected from one or more of sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, sodium methanesulfonate, sodium trifluoromethylsulfonate, sodium bisoxalate borate, sodium difluorooxalate borate, sodium difluorophosphate, sodium difluorobisoxalate phosphate, sodium bisfluorosulfonyl imide and sodium bistrifluoromethylsulfonyl imide; The organic solvent is selected from one or more of carboxylates, ethers, cyclic carbonates, and chain carbonates; The negative electrode is a hard carbon negative electrode material; The additive can form a stable interface film at the electrode / electrolyte interface. The interface film is a composite structure of organic and inorganic substances. The side close to the electrolyte is a loose porous part dominated by organic substances, which is beneficial to the infiltration of the electrolyte and the transmission of sodium ions. The side close to the electrode material is a dense part dominated by inorganic substances, which is beneficial to inhibiting the side reactions of the electrolyte. The additive can reduce the consumption of active sodium during the negative electrode film formation process, thereby facilitating the improvement of the first charging efficiency and the first capacity.
2. A sodium ion battery according to claim 1, characterized in that: The organic solvent is propylene carbonate, diethyl carbonate and ethyl methyl carbonate.
3. The sodium ion battery according to claim 1, characterized in that: The charging voltage of the sodium ion battery is ≤4.5V.
Citation Information
Patent Citations
Nonaqueous electrolyte solution for secondary batteries and nonaqueous electrolyte secondary battery
CN105009347A
Nonaqueous electrolyte solution for secondary battery and nonaqueous electrolyte secondary battery
US20160126592A1